High-to-Low CO(2) Acclimation Reveals Plasticity of the Photorespiratory Pathway and Indicates Regulatory Links to Cellular Metabolism of Arabidopsis - Timm, Stefan (Public Library of Science, 2012)
BACKGROUND: Photorespiratory carbon metabolism was long considered as an essentially closed and nonregulated pathway with little interaction to other metabolic routes except nitrogen metabolism and respiration. Most mutants of this pathway cannot survive in ambient air and require CO(2)-enriched air for normal growth. Several studies indicate that this CO(2) requirement is very different for individual mutants, suggesting a higher plasticity and more interaction of photorespiratory metabolism as generally thought. To understand this better, we examined a variety of high- and low-level parameters at 1% CO(2) and their alteration during acclimation of wild-type plants and selected photorespiratory mutants to ambient air. METHODOLOGY AND PRINCIPAL FINDINGS: The wild type and four photorespiratory mutants of Arabidopsis thaliana (Arabidopsis) were grown to a defined stadium at 1% CO(2) and then transferred to normal air (0.038% CO(2)). All other conditions remained unchanged. This approach allowed unbiased side-by-side monitoring of acclimation processes on several levels. For all lines, diel (24 h) leaf growth, photosynthetic gas exchange, and PSII fluorescence were monitored. Metabolite profiling was performed for the wild type and two mutants. During acclimation, considerable variation between the individual genotypes was detected in many of the examined parameters, which correlated with the position of the impaired reaction in the photorespiratory pathway. CONCLUSIONS: Photorespiratory carbon metabolism does not operate as a fully closed pathway. Acclimation from high to low CO(2) was typically steady and consistent for a number of features over several days, but we also found unexpected short-term events, such as an intermittent very massive rise of glycine levels after transition of one particular mutant to ambient air. We conclude that photorespiration is possibly exposed to redox regulation beyond known substrate-level effects. Additionally, our data support the view that 2-phosphoglycolate could be a key regulator of photosynthetic-photorespiratory metabolism as a whole.